Women, walls and memory: visual narratives of Guerrero feminism - CARREÓN GÓMEZ , Irma Georgina (Utopía y Praxis Latinoamericana, 2025)
This article explores how feminist murals created in Guerrero between 2019 and 2024 contribute to the construction of collective memory and feminist cultural heritage from a decolonial and descolonial perspective. In a context marked by femicides, forced marriages, displacement, and environmental crises, urban art emerges as a form of social protest and transformation. Using a qualitative methodology with a feminist narrative approach, the creative dynamics and production processes of the murals are examined from the perspective of the artists and communities. The findings reveal that these artistic expressions redefine public space and articulate affect, pedagogy, and political action. In emergency contexts, such as Hurricane Otis or the fight for legal abortion, the murals act as community accompaniment. It is concluded that feminist muralism in Guerrero generates symbolic territories of visual resistance and actively contributes to cultural transformation from a collective and aesthetic perspective.